Does doing good pay off? Social impact bonds and lessons for Islamic finance to serve the real economy - Syed Azman, Syed Marwan Mujahid; Haneef, Mohamed Aslam (Emerald Publishing, 2019)
Purpose – The purpose of this paper is to examine the world’s first social impact bond (SIB) and the lessons that can be learned for the Islamic finance industry to fulfil its true objectives. Design/methodology/approach – The Peterborough SIB was recently announced to be successful in achieving its targeted social and investment outcomes, reducing recidivism by 9 per cent and paying back investors a 3 per cent pa return. The paper compares Peterborough SIB with socially responsible investment (SRI) sukuk in terms of form and substance, and finds that there are various lessons from the Peterborough SIB that can be useful for future development of Islamic financial products. Findings – Innovative social financial tools such as SIB exemplify the true spirit of risk sharing and social responsibility, which is arguably missing in current practices of the Islamic finance industry. With the growing interest towards SRI strategies and increase in socially motivated investors, such financial tools may not only help the sustainable growth of the Islamic finance industry, but also fill in the gap between its theory and practice. Practical implications – As such, the paper also proposes a social impact sukuk model which integrates the key aspects learned from Peterborough SIB. This includes prioritising social impact, measurable success indicators, data and management systems, flexible contracts, third sector integration, risk sharing and fostering the culture of innovation. Originality/value – The findings can offer some practical insights in dealing with the issue of Islamic finance practice being overly concerned with its formal adherence with Islamic legal rules whilst neglecting its true fundamental values.